The accidental audience: industrial management of unexpected television viewerships - Burdfield, Claire (2017)
The Accidental Audience considers how media organizations construct and respond to audience members that are not part of the intended audience for a particular media product. Focusing on public service and commercial children’s television, this thesis explores how the increasing reliance on audience research and audience profiling, generating ideas of a constructed intended audience, can often oversimplify the unpredictable, messy and complex reality of television audiences. This thesis draws on critical work about industry conceptions of media audiences, notably the work of Philip Napoli, to develop a framework for conceptualizing the accidental audience. This focuses on the discrepancy between intended and actual audiences in the form of unexpected viewerships for (children’s) television programmes. Examining the television industry’s conceptualisation of audiences through the development of the TV ratings system, this thesis considers a series of case studies which introduce and utilise the model of the accidental audience. Specifically this thesis examines adult audiences of programming created for children, including the Brony audience (men aged 18-45) of My Little Pony: Friendship is Magic (2010- ), the student audience of Teletubbies (1997-2001), and the non-parent audience of Sesame Street (1969- ). In critical terms, this thesis explores how the television industry has responded in different ways to accidental audiences and examines the strategies used by the television industry to manage these audiences.